Pembuatan Pupuk Organik Cair (POC) - Inge Dwisvimiar; Rila Kusumaningsih; Efriyanto (Insan Kreasi Media, 2023)
Making liquid organic fertilizer, especially from organic waste with the addition of EM4 (Effective Microorganisms) bioactivators, aims to utilize beneficial microbial activity so that it has an impact on changing from less useful materials to useful products. The effect of time and materials of manufacture has an impact on the content in liquid organic fertilizer, and determines the effect of the EM4 bioactivator on the fertilizer content in liquid organic fertilizer. The method for making liquid organic fertilizer is organic waste such as lamtoro, tofu waste, dried blood, filter cake, straw, fish meal. husks and others separated from inorganic waste. Then add water and squeeze until the color turns clear. Bio sub is prepared and then mixed with urine with the aim of removing odors. All the ingredients that are already there are then mixed and stirred until evenly distributed. Put it in a bucket of paint and then ferment it for at least 14 to 30 days. At certain moments shaken the lid to remove air. The final stage is filtering and packaging. The application of liquid organic fertilizer (POC) can be sprayed on plant organs or watered/poured on the planting medium/soil. Prior to application, a minimum dilution of 1 versus 100 is carried out. If you need 1 liter of POC solution, 10 ml of POC is needed. The best time to apply POC is in the morning or evening.